Signature of two-electron interference in angular resolved double photoionization of Mg - Sokell, E.; Bolognesi, P.; Kheifets, A.; Bray, Igor; Safgren, S.; Avaldi, L. (The American Physical Society, 2013)
The double photoionization of Mg has been studied experimentally and theoretically in a kinematic where the two photoelectrons equally share the excess energy. The observation of a symmetrized gerade amplitude, which strongly deviates from the Gaussian ansatz, is explained by a two-electron interference predicted theoretically, but never before observed experimentally. Similar to the Cooper minima in the single photoionization cross section, the effect finds its origin in the radial extent and oscillation of the target wave function.